EFFECTS OF FISH PROCESSING METHODS ON CONSUMERS’ PREFERENCE IN GANYE TOWN, ADAMAWA STATE NIGERIA - JIDAUNA, S.B; QUAGER, J.T.; 2DZUEL, M.Y.; IBRAHIM, P.; MUSA, M.; MISAU, A.B. (Nigerian Journal of Fisheries, 2013)
A survey was conducted in August, 2012 to investigate the effects of fish species processing methods on consumers’ preference and by extension determine the relationship between fish species and consumers preference in Ganye town, with a view to provide baseline information for effective fish marketing in the area. A total of 125 wellstructured questionnaires were randomly administered to both processors (marketers) and consumers, but only 79 were correctly filled and data obtained were analyzed using descriptive statistics. Analysis of data showed 61% consumers and 87% smoked fish processors. Results implied that the business of fish processing has a good prospect in the area and the high number of smoked fish processors may not be unconnected with the abundance of wood-fuel as the cheapest energy source in the locality respectively. Consumers exhibited highest preference (59%) for smoked fish; this might be because of its characteristic strong flavor. It was therefore concluded that fish processing methods have effect on consumer’s preference in Ganye town. Fish species such as Mormyrus, Distichodus, etc. were the least preferred. This could be due to either one or all of the following reasons; excess fatty-oil content in the fish flesh, which are not considered to be first class food or numerous fine bones in the flesh that make them bothersome to eat, etc. The most preferred fish species in this study include Clarias gariepinus and Oreochromis niloticus. This might be adduced to their high relative abundance in the market, hence their affordability to most consumers.